TAKING INTO ACCOUNT THE PSYCHOLOGICAL CAPABILITIES OF A PERSON IN THE TEACHING OF TECHNICAL SCIENCES (American Journal of Research in Humanities and Social Sciences, 2025)
This article is devoted to studying the subtleties of reaction instructions and responses of the human brain in the educational process. And scientific conclusions and results of observations and experiments obtained as a result of monitoring the dependence of the speed of a person’s ability to read and sleep on personal characteristics and characteristics of the educational environment are presented.